Pulping of Poplars - Guha, S. R. D.; Sharma, Y. K.; Kumar, Krishan (Indian Forester, 1973)
The results of pulping of Populus × euranmericana Cv. 'casale', I 488, Populus deltoides IC and Populus × euramericana Cv. 'Heidemlj' by sulphate process are described. The average fibre length of Populus 'casale' was 902.24 µ, of Populus deltoides was 952.32 µ, and of Populus 'Heidemij' was 885.12 µ, and the average fibre diameter was 22.768 µ, 23.626 µ, and 23.210 µ respectively. All the three poplars gave excellent yields (between 50% to 57% based on oven-dry chips) and excellent strength properties (between 6.6 km to 12.6 km breaking length). Silviculturally, Populus deltoides IC appears to be most promising for large scale propagation.